CLINICAL AND PHARMACOECONOMIC REASONABILITY OF USING PROBIOTIC ENTEROCOCCUS STRAIN FOR THE COMPLEX DEVELOPMENTAL CARE PROGRAM FOR PREMATURE INFANTS - N. V. Gonchar; L. A. Lo Schiavo; A. N. Suvorov; N. P. Shabalov; A. S. Kolbin; A. P. Kasimova (Педиатрическая фармакология)
Introduction. Possibilities of using probiotic enterococci in premature neonates undergoing inpatient antibacterial therapy remains understudied. The article is aimed at analyzing clinical and pharmacoeconomic reasonability of using probiotic Enterococcus faecium L3 strain in premature infants with very low body weight in the framework of complex inpatient developmental care. Patients and methods. 55 children randomized into 2 groups were observed: the control group (n = 26) was undergoing standard developmental care program, the primary group (n = 29) was introduced liquid probiotic Enterococcus faecium L3 strain (titer — 108 CFU/ml or more) (0.5 ml TID for 14 days) after attaining the enteral feeding volume of 5.0 ml. Results. Analysis of the clinical symptoms characteristic of non-smooth course of developmental care over premature infants helped to reveal higher frequency of infectious complications in the control group children than in the primary group (14 [53.8%] vs. 6 [20.7%]; p < 0.05). Acute food intolerance was observed less frequently in the primary group than in the control group (6 [20.7%] vs. 10 [38.5%], p > 0.05). The primary group's children featured significant decrease in the frequency of monocytosis, positive changes of intestinal microbiotic composition (increase in the amount of bifidum bacteria, lactobacilli, enterococci, decrease in the amount of Clostridium difficile and antibiotic-resistant clinical Klebsiella pneumoniae strains). Conclusion. Favorable outcome of developmental care over premature infants (absence of infectious complications) was less expensive in the primary group's children.